Pedological Study and Classification of Some Soils Developed on Volcanic Rocks in Jerantut District, Pahang - Saleh, Ibrahim (1997)
Six soil profiles, comprising four soils developed over andesite and two developed over rhyolite were sampled in Jerantut District, State of Pahang. The soils were characterized by physical, chemical, mineralogical and micromorphological techniques. Classification of the soils were carried out according to Soil Taxonomy (USDA, 1996), FAO/UNESCO Legend (1990) and Malaysian Classification Systems (1992). In general, the particle size distribution, colour and some of chemical properties of the soils are directly associated with their parent materials and stage of weathering. The high clay content and redder colouration suggest an advanced stage of weathering and the presence of a high content of mafic minerals in the parent materials. Soil reaction is slightly acidic to moderately acidic in both parent materials with pH(water) ranging from 4.7 to 5.2 and with negative ll. pH values. The soils developed over andesite have a CEC ranging from 10 cmol(+)/kg soil to 15 cmol(+)/kg soil, while in rhyolitic soils, CEC ranges between 5 cmol(+)/kg soil and 10 cmol(+)/kg soil. The more weathered soils have base saturation less than 50% by NH40Ac. The organic carbon, nitrogen, available phosphorus and exchangeable Al content are low for all the soils studied. The free iron oxide content is higher for the soils derived from andesite which are deep soils when compared to soils on rhyolitic materials which are moderately deep soils. The free iron oxide of the soils is 'active' in nature based on the FejFed ratio of more than 0.05 except for one of the profiles over andesite (profile 1) which is less than 0.05 and reflected an advanced stage of weathering. Mineralogically, both of the parent materials are dominated by feldspar and quartz. Calcite, pyroxene, mica and chlorite are present as accessory minerals in andesite while rhyolite only contain chlorite and cristobalite. Kaolinite is the most dominant alumina-silicate clay mineral for these soils. Traces of interstratified layer and varying amount of feldspar, calcite, quartz, mica, halloysite and iron oxide are present. However, in one of the profile over andesite (profile 4), vermiculite is present in large quantity.